Type I Photosensitization with Strong Hydroxyl Radical Generation in NIR Dye Boosted by Vigorous Intramolecular Motions for Synergistic Therapy - Lin, Runfeng (Advanced materials (Deerfield Beach, Fla.), 2023)
© 2023 Wiley-VCH GmbH.